1999
DOI: 10.1007/s004330050121
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in superoxide dismutase, glutathione peroxidase and catalase activities in experimental cerebral ischemia-reperfusion

Abstract: Free radicals are thought to be the most important cause of the reperfusion injury subsequent to ischemia. The antioxidant status of the tissue affected by ischemia-reperfusion is of great importance for the primary endogenous defense against the free radical induced injury. This investigation was performed to evaluate the antioxidant enzyme capacity of the brain tissue in the ischemia-reperfusion period using an experimental global moderate (penumbral) ischemia model on rat brains. Experiments were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 36 publications
(40 reference statements)
4
33
1
Order By: Relevance
“…In the present study, SOD levels did not differ among groups. This is not consistent with some reports of cerebral I/R studies [42,43,44]. However, there are conflicting reports.…”
Section: Discussioncontrasting
confidence: 56%
“…In the present study, SOD levels did not differ among groups. This is not consistent with some reports of cerebral I/R studies [42,43,44]. However, there are conflicting reports.…”
Section: Discussioncontrasting
confidence: 56%
“…Equally important, they likely activate specific signaling pathways that initiate adaptive or death responses (8). This ability to control ROS is critical in stroke, and neuronal damage occurs if the ''oxidant-antioxidant'' balance is disturbed in favor of excess oxidative stress during ischemia/ reperfusion (9,10). Therefore, ROS management plays a central role in the pathogenesis of stroke.…”
mentioning
confidence: 99%
“…Similar to our study, it is demonstrated that ischemic circumstances lead to the accumulation of hypoxanthine and stimulates XO activity [29] . The activity of GSH-Px, which detoxifies H 2 O 2 while oxidizing reduced GSH to oxidized GSSG, was depressed during I/R [4] . In the present study, cerebral cortex GSH-Px activity significantly decreased after 24 h ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Transient focal and global cerebral I/R triggers a plethora of cellular and molecular events that promotes neuronal cell death in several regions of the brain due to glutamate excitotoxicity, oxidative stress, inflammation and apoptosis [1][2][3][4] . Studies show that nitric oxide (NO) has beneficial properties to I/R injury including increase of blood flow produced by cerebral vasodilatation and inhibition of inflammation [1,5] .…”
Section: Introductionmentioning
confidence: 99%